Global and regional financial safety nets: Lessons from Europe and Asia - Changyong Rhee; Lea Sumulong; Shahin Vallée (Bruegel, 2013)
The Asian financial crisis (1997) and the European crisis (2009) have both contributed to the development and deepening of regional safety net arrangements. This paper analyses the relationships between global and regional financial safety nets, and uncovers the potential tensions and operational challenges associated with the involvement of several institutional players with potentially different interests, analytical biases and governance. The G20 has acknowledged the importance of these new players for the international monetary system, but the principles for cooperation between the IMF and regional financing arrangements are far too broad and ad hoc to contribute to a coherent and effective architecture. This paper tries to establish some lessons learned from the Asian financial crisis in 1997 and the current European crisis in order to enhance the effectiveness, efficiency, equity and governance of these arrangements. In particular, it proposes changes to the IMF articles of agreement to allow for lending or guarantees to regional arrangements directly and it establishes some key desirable features and practices of regional mechanisms that should be adopted everywhere to ensure some global consistency, particularly in the field of macroeconomic surveillance, programme design and conditionality.
Keywords: 330; Finanzkrise; EU-Finanzbeziehungen; Internationale Finanzhilfe; Asien; Europa